2001
DOI: 10.22260/isarc2001/0047
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Simulation Results in the Economic Analysis of Robotized Construction Tasks

Abstract: Abstract:Adequate economic justification is a key requirement for the implementation of robotic systems in the construction industry. In the present work the concept of off-line simulation is used to provide the user with a rational approach for economic decision making with regard to the use of robotics. The proposed off-line simulation process helps the user in planning, scheduling and costing the whole job. With the aid of a graphical simulation package, the user can estimate the whole job time that reflect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Earlier study carried out by Zied et al (2001) on the economic feasibility of the use of Starlifter robotic system in core drilling underneath a motorway bridge showed that the robotic solution is more economic in the short term based on hiring the system. The study was based on cost estimation based on graphical simulation of the proposed system.…”
Section: Feasibility Analysis Modelmentioning
confidence: 99%
“…Earlier study carried out by Zied et al (2001) on the economic feasibility of the use of Starlifter robotic system in core drilling underneath a motorway bridge showed that the robotic solution is more economic in the short term based on hiring the system. The study was based on cost estimation based on graphical simulation of the proposed system.…”
Section: Feasibility Analysis Modelmentioning
confidence: 99%
“…3) Off-line simulation: The required tooling for the project is established and a 3D simulation of the required operations is carried out. The output is a job report which includes the system modules such as locomotion, tools, sensors etc., a work schedule and economic analysis, a preprogrammed set of tasks produced by the off-line simulation for use on site (Seward and Zied 2001). 4) Site operation-preliminary positioning: The robot is placed near the task area within its working envelope using an appropriate mobile platform, for example, telescopic boom.…”
Section: Typical Working Scenario Of Starlifter Robotmentioning
confidence: 99%
“…A list of the simulated tasks can be then passed to the next module for planning and scheduling as shown in Figure 12. The final step is to calculate the cost of the whole job using the simulation time for each task and the cost of the equipment and labor involved in the process (Seward and Zied, 2001). A final report on the whole job can then be produced.…”
Section: ) the Sensor Software Modulementioning
confidence: 99%